Syntheses of the C(1-6) and C(19-24) fragments of lituarines A, B, and C. - Robertson, J; Dallimore, J; Meo, P (2004)
[structure: see text] Lituarines A-C are marine natural products comprising a tricyclic spiroacetal bridged at C(8) and C(18) by a functionalized ester linkage conceptually obtained from a C(19-24) alcohol and a C(1-6) carboxylic acid whose oxidation level varies at C(4) and C(5). Stereoselective routes are described to compounds 26 and 27, fully functionalized ester fragments of lituarine A and lituarines B and C, respectively.